Stock market linkages in Asia. Revisiting Granger causality evidences - T.G. SAJI (Theoretical and Applied Economics, 2022)

(untitled)
In this research, using the most recent daily stock index data of Japan, Singapore, South Korea, India and China, we revisit the financial integration in Asia. The study applies Granger causality and Impulse Response Function to analyse the pattern of equity market integration in the region. The findings of the study reveal that price convergence among Asian stock markets is still relatively weak. In general, causality is unidirectional and existing among most markets with shortlived impacts. The asymmetrical price behaviour of Asian markets has implications for the pricing efficiency of national markets and suggests many opportunities for global investors to optimize returns through market diversifications on a long-term perspective.